Prostate cancer: 1. The descriptive epidemiology in Canada - Levy, I G (1998)
A 70-year-old woman who experienced a long period of depression after her first husband's death from prostate cancer at the age of 63 has become increasingly anxious about her own health and that of her close family. A few years ago she married a man her own age; he is in good physical condition. Last year the family spent much of the winter in Florida, where the woman noticed several studies in the media suggesting that an epidemic of prostate cancer is occurring in North America and that because early detection can save lives men of retirement age should be checked by their physicians as soon as possible. In addition, 2 close friends recently diagnosed with prostate cancer. On his latest fishing trip her husband learned from a friend that 1 in 8 men get prostate cancer. He has not seen his family physician for several years, but his wife has booked an appointment for them to discuss their concerns.